2008
DOI: 10.1002/glia.20785
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α‐ and TRAIL‐resistant glioma cells undergo autophagy‐dependent cell death induced by activated microglia

Abstract: The role of microglia, the brain resident macrophages, in glioma biology is still ill-defined. Despite their cytotoxic potential, these cells that significantly infiltrate the tumor mass seem to support tumor growth rather than tumor eradication. A proper activation of microglia anti-tumor activities within the tumor may provide a valuable additional arm of defense to immunotherapies against brain tumors. We herewith report a detailed characterization of (lipopolysaccharide and interferon-gamma)-induced anti-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 66 publications
2
47
0
Order By: Relevance
“…Of note, we showed that the effect observed is higher than the direct effect of Paclitaxel alone. In 3D co-culture experiments, untreated or treated with low doses of Paclitaxel, macrophages supported the growth and invasion of glioma cells (Figure 7Ab), as expected from previous observations with murine microglia and human tumorassociated microglia/macrophages 68,69 . We showed that these supportive activities were suppressed by a pre-treatment of macrophages with Paclitaxel, which triggered an efficient antitumor response.…”
Section: Discussionsupporting
confidence: 87%
“…Of note, we showed that the effect observed is higher than the direct effect of Paclitaxel alone. In 3D co-culture experiments, untreated or treated with low doses of Paclitaxel, macrophages supported the growth and invasion of glioma cells (Figure 7Ab), as expected from previous observations with murine microglia and human tumorassociated microglia/macrophages 68,69 . We showed that these supportive activities were suppressed by a pre-treatment of macrophages with Paclitaxel, which triggered an efficient antitumor response.…”
Section: Discussionsupporting
confidence: 87%
“…The capacity of EGCs for phagocytosis and cytokine-inducible HLA-DR complex class II expression, which is fully functional for antigen-specific T-cell activation, has been confirmed in tissue culture experiments [36]. The EGCs are morphologically and molecularly similar to CNS astrocytes [37,38]; thus, they presumably share some functions with these cells, such as structural, metabolic, trophic, and protective support of neurons [39].…”
Section: Discussionmentioning
confidence: 88%
“…[29][30][31] Nevertheless, some studies have found that tumors easily build resistance to TRAIL-based therapies. 32,33 Tumor cell resistance to TRAIL seemed to occur through the modulation of various molecular targets, including differential expression of death receptors, overexpression of anti-apoptotic molecules, mutations in apoptotic genes, defected in caspase signaling, and caspase inhibition in resistant cells. 34,35 In this study, we expressed TRAIL delivered by rNDV to improve the effect of cancer therapy.…”
Section: Discussionmentioning
confidence: 99%